Electron-beam patterned self-assembled monolayers as templates for Cu electrodeposition and lift-off - She, Zhe; DiFalco, Andrea; Hähner, Georg; Buck, Manfred (Beilstein Journal of Nanotechnology, 2012)
Self-assembled monolayers (SAMs) of 4'-methylbiphenyl-4-thiol (MBP0) adsorbed on polycrystalline gold substrates served as templates to control electrochemical deposition of Cu structures from acidic solution, and enabled the subsequent lift-off of the metal structures by attachment to epoxy glue. By exploiting the negative-resist behaviour of MBP0, the SAM was patterned by means of electron-beam lithography. For high deposition contrast a two-step procedure was employed involving a nucleation phase around −0.7 V versus Cu2+/Cu and a growth phase at around −0.35 V versus Cu2+/Cu. Structures with features down to 100 nm were deposited and transferred with high fidelity. By using substrates with different surface morphologies, AFM measurements revealed that the roughness of the substrate is a crucial factor but not the only one determining the roughness of the copper surface that is exposed after lift-off.
Keywords: electrochemical nanotechnology; electrodeposition; lithography; metallic nanostructures; self-assembled monolayers; thiols

(untitled) - Choi, J.; Lee, K.; Janes, D. B. (Nano Lett., 2004)

(untitled) - Hu, J.; Yu, M.-F. (Science, 2010)

Electroanalytical Chemistry: A Series of Advances - Finklea, H. O. (Electrochemistry of Organized Monolayers of Thiols and Related Molecules on Electrodes, 1996)

(untitled) - Goldenberg, L. M.; Bryce, M. R.; Petty, M. C. (J. Mater. Chem., 1999)

Chemically Modified Electrodes - Gooding, J. J.; Lai, L. M. H.; Goon, I. Y. (Nanostructured Electrodes with Unique Properties for Biological and Other Applications, 2009)

(untitled) - Penner, R. M. (MRS Bull., 2010)

(untitled) - Huang, S.; Chen, Y. (Nano Lett., 2008)

(untitled) - Salaün, P.; Planer-Friedrich, B.; van den Berg, C. M. G. (Anal. Chim. Acta, 2007)

(untitled) - Barnes, W. L.; Dereux, A.; Ebbesen, T. W. (Nature, 2003)

(untitled) - Nagpal, P.; Lindquist, N. C.; Oh, S.-H.; Norris, D. J. (Science, 2009)

(untitled) - Mühlschlegel, P.; Eisler, H.-J.; Martin, O. J. F.; Hecht, B.; Pohl, D. W. (Science, 2005)

(untitled) - Yu, N.; Cubukcu, E.; Diehl, L.; Belkin, M. A.; Crozier, K. B.; Capasso, F.; Bour, D.; Corzine, S.; Höfler, G. (Appl. Phys. Lett., 2007)

(untitled) - Zach, M. P.; Ng, K. H.; Penner, R. M. (Science, 2000)

(untitled) - Loo, Y.-L.; Willett, R. L.; Baldwin, K. W.; Rogers, J. A. (Appl. Phys. Lett., 2002)

(untitled) - Thom, I.; Hähner, G.; Buck, M. (Appl. Phys. Lett., 2005)

(untitled) - Schilardi, P. L.; Azzaroni, O.; Salvarezza, R. C. (Langmuir, 2001)

(untitled) - Schilardi, P. L.; Dip, P.; dos Santos Claro, P. C.; Benítez, G. A.; Fonticelli, M. H.; Azzaroni, O.; Salvarezza, R. C. (Chem.–Eur. J., 2005)

(untitled) - Haick, H.; Cahen, D. (Prog. Surf. Sci., 2008)

(untitled) - Azzaroni, O.; Fonticelli, M.; Schilardi, P. L.; Benítez, G.; Caretti, I.; Albella, J. M.; Gago, R.; Vázquez, L.; Salvarezza, R. C. (Nanotechnology, 2004)

(untitled) - Azzaroni, O.; Fonticelli, M. H.; Benítez, G.; Schilardi, P. L.; Gago, R.; Caretti, I.; Vázquez, L.; Salvarezza, R. C. (Adv. Mater., 2004)

(untitled) - Weckenmann, U.; Mittler, S.; Krämer, S.; Aliganga, A. K. A.; Fischer, R. A. (Chem. Mater., 2004)

(untitled) - Walker, A. V. (Langmuir, 2010)

(untitled) - Bhuvana, T.; Kulkarni, G. U. (Bull. Mater. Sci., 2008)

(untitled) - Nottbohm, C. T.; Turchanin, A.; Gölzhäuser, A. (Z. Phys. Chem., 2008)

(untitled) - Felgenhauer, T.; Yan, C.; Geyer, W.; Rong, H.-T.; Gölzhäuser, A.; Buck, M. (Appl. Phys. Lett., 2001)

(untitled) - Völkel, B.; Kaltenpoth, G.; Handrea, M.; Sahre, M.; Nottbohm, C. T.; Küller, A.; Paul, A.; Kautek, W.; Eck, W.; Gölzhäuser, A. (Surf. Sci., 2005)

(untitled) - Xiang, C. X.; Kung, S.-C.; Taggart, D. K.; Yang, F.; Thompson, M. A.; Güell, A. G.; Yang, Y. A.; Penner, R. M. (ACS Nano, 2008)

(untitled) - Zeira, A.; Berson, J.; Feldman, I.; Maoz, R.; Sagiv, J. (Langmuir, 2011)

(untitled) - Sondag-Huethorst, J. A. M.; Fokkink, L. G. J. (Langmuir, 1995)

(untitled) - Sondag-Huethorst, J. A. M.; van Helleputte, H. R. J.; Fokkink, L. G. J. (Appl. Phys. Lett., 1994)

(untitled) - O'Brien, B.; Stebe, K. J.; Searson, P. C. (J. Phys. Chem. C, 2007)

(untitled) - Pesika, N. S.; Radisic, A.; Stebe, K. J.; Searson, P. C. (Nano Lett., 2006)

(untitled) - Kaltenpoth, G.; Völkel, B.; Nottbohm, C. T.; Gölzhäuser, A.; Buck, M. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2002)

(untitled) - Love, J. C.; Estroff, L. A.; Kriebel, J. K.; Nuzzo, R. G.; Whitesides, G. M. (Chem. Rev., 2005)

(untitled) - Smith, R. K.; Lewis, P. A.; Weiss, P. S. (Prog. Surf. Sci., 2004)

(untitled) - Shen, C.; Buck, M. (Nanotechnology, 2009)

(untitled) - Turchanin, A.; Schnietz, M.; El-Desawy, M.; Solak, H. H.; David, C.; Gölzhäuser, A. (Small, 2007)

(untitled) - Klauser, R.; Huang, M.-L.; Wang, S.-C.; Chen, C.-H.; Chuang, T. J.; Terfort, A.; Zharnikov, M. (Langmuir, 2004)

(untitled) - Geyer, W.; Stadler, V.; Eck, W.; Zharnikov, M.; Gölzhäuser, A.; Grunze, M. (Appl. Phys. Lett., 1999)

(untitled) - Zharnikov, M.; Grunze, M. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2002)

(untitled) - Baunach, T.; Ivanova, V.; Kolb, D. M.; Boyen, H.-G.; Ziemann, P.; Büttner, M.; Oelhafen, P. (Adv. Mater., 2004)

(untitled) - Shekhah, O.; Busse, C.; Bashir, A.; Turcu, F.; Yin, X.; Cyganik, P.; Birkner, A.; Schuhmann, W.; Wöll, C. (Phys. Chem. Chem. Phys., 2006)

(untitled) - Silien, C.; Lahaye, D.; Caffio, M.; Schaub, R.; Champness, N. R.; Buck, M. (Langmuir, 2011)

(untitled) - Azzaroni, O.; Schilardi, P. L.; Salvarezza, R. C. (Appl. Phys. Lett., 2002)

(untitled) - Azzaroni, O.; Schilardi, P. L.; Salvarezza, R. C. (Electrochim. Acta, 2003)

Electrocrystallization in Nanotechnology - Staikov, G. (Wiley-VCH, 2007)

Chemically Modified Electrodes - Buck, M. (Structure, Electrochemistry and Applications of Self-Assembled Monolayers of Thiols, 2009)

(untitled) - Silien, C.; Buck, M. (J. Phys. Chem. C, 2008)

(untitled) - Pattanaik, G.; Shao, W. B.; Swami, N.; Zangari, G. (Langmuir, 2009)

(untitled) - Langerock, S.; Ménard, H.; Rowntree, P.; Heerman, L. (Langmuir, 2005)

(untitled) - Azzam, W.; Fuxen, C.; Birkner, A.; Rong, H.-T.; Buck, M.; Wöll, C. (Langmuir, 2003)

(untitled) - Schilardi, P.; Méndez, S.; Salvarezza, R. C.; Arvia, A. J. (Langmuir, 1998)

(untitled) - Heinze, J. (Angew. Chem., Int. Ed., 1993)

(untitled) - Tai, Y.; Shaporenko, A.; Grunze, M.; Zharnikov, M. (J. Phys. Chem. B, 2005)

(untitled) - Andricacos, P. C.; Uzoh, C.; Dukovic, J. O.; Horkans, J.; Deligianni, H. (IBM J. Res. Dev., 1998)

(untitled) - Moffat, T. P.; Wheeler, D.; Edelstein, M. D.; Josell, D. (IBM J. Res. Dev., 2005)

(untitled) - Munoz, R. C.; Vidal, G.; Mulsow, M.; Lisoni, J. G.; Arenas, C.; Concha, A.; Mora, F.; Espejo, R.; Kremer, G.; Moraga, L.; Esparza, R.; Haberle, P. (Phys. Rev. B, 2000)

(untitled) - Satterley, C. J.; Lovelock, K. R. J.; Thom, I.; Dhanak, V. R.; Buck, M.; Jones, R. G. (Surf. Sci., 2006)

(untitled) - Baserga, A.; Vigano, M.; Casari, C. S.; Turri, S.; Li Bassi, A.; Levi, M.; Bottani, C. E. (Langmuir, 2008)

(untitled) - Wagner, P.; Hegner, M.; Guentherodt, H.-J.; Semenza, G. (Langmuir, 1995)